Equipping the Young Generation with Modern Accounting Skills using Zahir Accounting - Ismawati; Masrullah; Indriana; Nurinaya; Sitti Marhumi; Saida Said (www.amertainstitute.com, 2025)
The rapid advancement of digital technology and the increasing demand for industry-relevant competencies have transformed the field of accounting, shifting practices from manual processes to computerized systems. This community engagement program aims to strengthen the technological and accounting competencies of students at SMA Muhammadiyah 1 Unismuh Makassar by introducing Zahir Accounting as a modern, practical, and industry-recognized accounting software. The program responds to a significant skills gap, where many students lack exposure to accounting applications commonly used in professional settings. Through a one-day intensive workshop conducted at the Faculty of Economics and Business, Universitas Muhammadiyah Makassar, participants received training on financial management concepts, software navigation, and the preparation of complete financial statements using Zahir Accounting. The activity included theoretical lectures, hands-on tutorials, and guided simulations to ensure students gained both conceptual understanding and practical experience. Findings from the program indicate substantial improvements in students’ digital literacy, financial reporting skills, and awareness of technology-based accounting practices. Moreover, the training enhanced students’ confidence and preparedness to enter the workforce or pursue entrepreneurial endeavors, aligning with Muhammadiyah’s vision of developing competent, values-driven human resources. The program demonstrates the relevance of integrating modern accounting tools into secondary education and highlights the need for continuous training and the development of tailored learning modules to ensure long-term impact and sustainability.